Ethical considerations of genetic and genomic testing in pediatric oncology: A narrative review - Brittany L. Greene; Jonathan M. Marron (CA: A Cancer Journal for Clinicians, 2026)
Abstract Genomics—and genomic testing in particular—has transformed oncology, facilitating both targeted therapies and personalized care. In pediatric oncology, unique clinical and ethical considerations arise. Compared with adults, children and adolescents are affected by more limited evidence regarding test performance, variant interpretation, and the clinical utility of genomically informed interventions. Nevertheless, genomic findings may have implications beyond the patient, affecting their parents, siblings, and other relatives and raising questions around consent, assent, privacy, and psychosocial impact. This narrative review examines how ethical dimensions of genetic and genomic testing evolve across the pediatric cancer continuum, from diagnosis and treatment through survivorship and transition to adult care. Attention is given to communication strategies, interdisciplinary support, and equity concerns that influence the responsible integration of genomic medicine. The authors also identify priority areas for future inquiry, including incorporation of children's perspectives, longitudinal approaches to recontact and reconsent, and better understanding of how genomic information affects treatment decision‐making. Pediatric genetic and genomic testing in oncology holds great promise, but its benefits can only be realized through thoughtfully developed and standardized communication practices, careful ethical deliberation, and equitable implementation. By proactively addressing these issues, pediatric oncologists can harness genomic advances in ways that respect and support children and their families.